'Strategic Constitutions': Constitutional Change and Politics in Pakistan. Issue 3 (3rd July 2017) - Ahmed, Imran
ABSTRACT: This paper argues that constitutions can play an important role in fostering a degree of political co-operation if they are useful to the political strategies of both rulers and ruled. Viewing Pakistan's constitutional documents as 'strategic constitutions' helps to explain the timing and content of constitutional reform, but also the seemingly contradictory provisions relating to the Constitutions' commitment to Islam. A strategic constitution functions to settle political exigencies rather than committing itself to the task of putting fundamental issues of state to rest. Often, the constitutional domain substitutes for other conventional channels of politics which may be inaccessible, or deliberately sidestepped, in order to achieve particular political goals.